1978
DOI: 10.1346/ccmn.1978.0260607
|View full text |Cite
|
Sign up to set email alerts
|

The Release of Aluminum from Aluminosilicate Minerals. I. Kinetics

Abstract: Abstract--The rates of release of AI by M NH~NO3 (pH 3) from minerals saturated with AI ions at pH 3 suggest that AI ions migrated from the surface layers and the matrix cores of kaolinite, montmorillonite, illite, and biotite, but only from the matrix core of muscovite mica. From the 0.25-0.5 p.m kaolinite and montmorillonite, part of the 'surface' A1 is released 'instantaneously' and the rest by first order kinetics, but the coarse 1.5-2.5 ttm kaolinite has only the former component. From illite and biotite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Parabolic kinetics have been observed for the dissolution of a wide variety of silicate minerals including 2:l phyllosilicates (Newman and Brown, 1969;Huang and Keller, 1973;Cabrera and Talibudeen, 1978) and can be interpreted in terms of diffusion mechanisms (Luce et al, 1972;Grandstaff, 1977). Parabolic kinetics can also be explained in terms of the precipitation of reaction products (Holdren and Adams, 1982), or changing surface areas (Holdren and Berner, 1979;Schott et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Parabolic kinetics have been observed for the dissolution of a wide variety of silicate minerals including 2:l phyllosilicates (Newman and Brown, 1969;Huang and Keller, 1973;Cabrera and Talibudeen, 1978) and can be interpreted in terms of diffusion mechanisms (Luce et al, 1972;Grandstaff, 1977). Parabolic kinetics can also be explained in terms of the precipitation of reaction products (Holdren and Adams, 1982), or changing surface areas (Holdren and Berner, 1979;Schott et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The dissolution kinetics of micas has been found to be both linear (Gastuche, 1963) and parabolic (Cabrera and Talibudeen, 1978;Huang and Keller, 1973;Newman and Brown, 1969). Huang and Keller (1973) also found that Si had the slowest release rate from illite.…”
Section: Kineticsmentioning
confidence: 99%
“…The relevant properties of the minerals used in this work are listed in Table 1 ; (for a fuller description, see Cabrera and Talibudeen, 1978). Potentiometric tit~ AI( N03)3 solution.…”
Section: Mineralsmentioning
confidence: 99%
“…Therefore, little can be said, in a quantitative sense, about the nature of adsorbed AI ions from such potentiometric titration. However, the observation of the more complex buffering of adsorbed A1 than of Ai in solution points to its resistance to reaction with added OH-ions because of the strong binding of AI a § and to the existence of hydroxy-polymeric AI (Cabrera and Talibudeen, 1978) on mineral surfaces, which therefore titrate at higher pH values.…”
Section: Clays and Clay Mineralsmentioning
confidence: 99%
See 1 more Smart Citation